(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The paper presents possible antecedents of the creation of higher education courses in the field of fashion in Brazil, also characterized as fashion design. It seeks to show that this path is intertwined with the teaching of drawing, manual crafts, arts and design. Thus, it is proposed to think about this trajectory of origin to better understand the bases of contemporary education, as well as the challenges faced in Brazil in the area of fashion design. This is a bibliographical study of the founding history of higher education courses in the area of fashion design in Brazil. It is based on the work of Pires (2002), Mattos (2015), Moura and Lago (2015) and Aguiar (2015). Finally, it is identified that the teaching of fashion design enters the academy initially through specific courses within other graduations, followed by extension courses and only in mid-1987 as a bachelor degree.